The Drawing of the Mark of Cain A Socio-historical Analysis of the Growth of Anti-Jewish Stereotypes - van Arkel, Dik (Amsterdam University Press, 2009)
Antisemitism is an exceptional historical phenomenon. Its history goes back at least 2000 years and has manifested itself in many countries and in a wide range of societies. However, it is not a universal phenomenon. Many countries have no tradition of anti-Semitism and even in those where anti-Semitism periodically raises its head, there have been long periods where it appears to have lain dormant. But it has never altogether disappeared, and all the large-scale social changes of the past two millennia have given it extra impetus. This definitive study tackles the complex roots and manifestations of anti-Semitism over the centuries, tracing the rise of anti-Jewish stereotypes and the circumstances in which racial prejudice may have tragic concequences. This book will quickly become a classic text for students and researchers in this persistent and worldwide prejudice.